Power control strategy for PV/Wind reverse osmosis desalination without battery. (August 2019) - Khiari, Wahib; Turki, Mehdi; Belhadj, Jamel
Abstract: The goal of this paper is to develop and validate a novel power control strategy allowing to operate a Brackish Water Reverse Osmosis (BWRO) desalination test bench properly using isolated hybrid (PV/Wind) renewable sources without batteries. The proposed strategy uses Power Field Oriented Control (PFOC) in order to maintain DC bus voltage stability and to ensure power transfer from electrical sources to hydro-mechanical loads under variable power generation conditions. Experimental performances have been tested in different operating modes while respecting a Safe Operating Window (SOW) for desalination process. Power sharing is ensured by a basic Energy Management System (EMS). Highlights: Control & energy management for batteryless RE-RO desalination is proposed. Energy storage in batteries is replaced with water storage in tank. The control allows stabilizing V d c & controlling motor-pumps electrical power. Energy management system allows optimizing power sharing between motor-pumps.